Dynamic Spectrum Auction in Wireless Communication - Chen, Yanjiao; Zhang, Qian (SpringerBriefs in Electrical and Computer Engineering, 2015)
This brief explores current research on dynamic spectrum auctions, focusing on fundamental auction theory, characteristics of the spectrum market, spectrum auction architecture and possible auction mechanisms. The brief explains how dynamic spectrum auctions, which enable new users to gain spectrum access and existing spectrum owners to obtain financial benefits, can greatly improve spectrum efficiency by resolving the artificial spectrum shortage. It examines why operators and users face significant challenges due to specialty of the spectrum market and the related requirements imposed on the auction mechanism design. Concise and up-to-date, Dynamic Spectrum Auction in Wireless Communication is designed for researchers and professionals in computer science or electrical engineering. Students studying networking will also find this brief a valuable resource.